Is Cancer Inevitable? - Weeraratna, Ashani T. (Johns Hopkins University Press, 2021)
How can new understandings about cancer cell interactions help doctors better control, and eventually cure, cancer?Cancer is a formidable enemy. In fact, people born in America since 1960 face a one in two chance of being diagnosed with cancer in their lifetimes. However, there's growing evidence that fewer cancers will be death sentences for patients. New approaches and understandings are transforming the medical world, increasing success rates for remissions, disease management, and cures. Dr. Ashani Weeraratna is at the forefront of this new level of care. In Is Cancer Inevitable?, Weeraratna-a pioneering melanoma researcher whose work explores the role aging plays in cancer cells' spread and drug resistance-gives readers an inside look at several of the latest cancer advances. Detailing the actions that are reducing the disease's impact and exploring what the future may hold, she explains how the molecular mechanisms involved in metastasis and the cells' microenvironments influence cancer's development and progression. Over the years, she writes, our understanding of how cancer cells move throughout the body, change as they plant themselves in the body's microenvironments, and even communicate with one another have led to major insights about how cancer works. With compelling detail, she takes us inside her lab, revealing how new insights are leading to major breakthroughs, even among patients with Stage IV cancer. She also explains how age-related changes in the microenvironment contribute to multiple aspects of melanoma formation and development. Such scholarship, she argues, is moving us toward a day when more patients will be declared cancer-free. An inspiring and deeply personal book, Is Cancer Inevitable? offers readers newfound hope.Features• Explores key insights and studies developed in recent years that have greatly influenced the world of cancer research, including how aging microenvironments within our bodies encourage metastasis and therapy resistance• Guides readers through Dr. Ashani Weeraratna's personal story of coming to the United States from Lesotho at the age of 17 and rising to become one of the pioneers in her field• Brings readers inside Weeraratna's lab, describing both the processes and the missions of her work • Raises awareness about how cancer works within the body and what any patient or family encountering the disease needs to understand-while also offering them hope based on new and forthcoming diagnostic and treatment methods• Outlines why we will never control-let alone cure-cancer if we don't find a common purpose and come together in collaboration, inviting the greatest minds from around the world to participate in finding and implementing solutionsJohns Hopkins WavelengthsIn classrooms, field stations, and laboratories in Baltimore and around the world, the Bloomberg Distinguished Professors of Johns Hopkins University are opening the boundaries of our understanding of many of the world's most complex challenges. The Johns Hopkins Wavelengths book series brings readers inside their stories, illustrating how their pioneering discoveries benefit people in their neighborhoods and across the globe in artificial intelligence, cancer research, food systems' environmental impacts, health equity, science diplomacy, and other critical arenas of study. Through these compelling narratives, their insights will spark conversations from dorm rooms to dining rooms to boardrooms.